A novel colchicine-myricetin heterozygous molecule: design, synthesis, and effective evaluations on the pathological models of acute lung injury in vitro and in vivo - Li, Zhiyue; Yan, Xueqin; Wei, Jiangchun; Pu, Liuyang; Zhu, Guanbao; Cao, Yongkai; Liu, Zhanyan; Liu, Yaqian; Li, Yan; Li, Limin; Li, Xinping; Wu, Zhengzhi (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is an inflammatory condition and there are no effective treatments. A novel new compound----colchicine-myricetin hybrid (CMyrH) was herein designed and synthesized. To evaluate the activity of CMyrH in ALI, we used a bleomycin (BLM) induced BEAS-2B injury model in vitro and established a well-recognized rat model of BLM-induced lung injury in vivo. The results demonstrated that colchicine-myricetin hybrid protected BEAS-2B cells against BLM-induced cell injury in an increased dose manner, and reduced wet/dry weight ratio, histological scoring, and inflammation cytokines IL-1β, IL-6, IL-18, and TNF-α levels of lung tissue of the rats. Furthermore, we found colchicine-myricetin hybrid inhibited caspase-1, ASC, GSDMD, and NLRP-3 expression in vivo. Meanwhile, we used molecular docking to analyze the binding mode of colchicine-myricetin hybrid and human neutrophil elastase (HNE), it revealed that colchicine-myricetin hybrid showed strong binding affinity toward human neutrophil elastase when compared to its parent molecules. In conclusion, It is suggested that colchicine-myricetin hybrid antagonized acute lung injury by focusing on multi-targets via multi-mechanisms, and might be served as a potential therapeutic agent for acute lung injury.